Analisa Reformulasi IKPA terhadap Pengawasan Pengelolaan Kinerja Keuangan Kementerian Agama - Sri Rahayu, Yayuk (Department of Public Administration, 2023)
IKPA is an indicator set by the Ministry of Finance to measure the quality of the performance of national ministries/institutions' budget implementation, including compliance with plans, effectiveness of budget execution, efficiency of budget execution, and compliance. In 2022, the Ministry of Finance will change the paradigm of evaluating the performance of budget execution, from previously focusing on improving budget execution governance to support accelerated spending and output results, focusing on improving the quality of spending, so that it can contribute to the formation of economic results by providing the best contribution and social welfare. . This was then formulated in the form of a 2022 IKPA reformulation. This study aims to determine the effect of IKPA on oversight of financial performance management at the Ministry of Religion. The method in this study is a secondary qualitative research method. The research results show that the results of the evaluation in the third quarter of 2022, the aggregate IKPA score has reached a value of 92.88. this reflects that the governance of budget execution is maintained well.